Performance practice of modern Chinese orchestra in Malaysia - Chew, Yi Tien (2013)
The fast growing number of modern Chinese orchestras in the country has promoted this study to be conducted, as the purpose and function of the modern Chinese orchestra as a cultural entity could possibly be different to that of an educational setting. This research will investigate the historical background and origins of the modern Chinese orchestra in schools in Malaysia, to examine the performance practice of the modern Chinese orchestra in Malaysia and to discuss issues in performance and interpretation of the modern Chinese orchestra in secondary schools. This study was conducted qualitatively with usage of techniques such as observations, semi-structured interviews and video analysis. The primary setting of this study was the modern Chinese orchestra of the selected four schools; SMJK Yu Hua, Kajang, SMK PJ Katolik, SMK Taman Connaught and Kuen Cheng High School while the secondary setting of this study are the activities related to this four schools’ modern Chinese orchestra; mainly their activities such as the performances and competitions that they participated in. The repertoires used by the four schools’ modern Chinese orchestra originate from different cultures with the Chinese culture being the predominant culture. An interesting discovery was that these repertoires is very closely related to the culture which they originate from thus it is often not possible to perform these music if the musicians themselves are not familiar with the cultural connotations which is being carried by the repertoire itself. There are however contradicting practices in terms of notations used for these repertoires. While the repertoire itself is very much culturally and historically orientated, the notation used in these repertoire is predominantly the western style stave notation while the orchestration and sitting arrangement has strong similarities to that of the western symphony orchestra. This practice has also created certain implications to the ability of the musicians to execute the musical nuances, understanding of their role within the orchestra and ultimately produce an expressive and culturally informed performance. These practices have also led to some intriguing discussion on the interpretative process. Factors influencing the interpretative process and decisions were discussed as many of the repertoires used by the modern Chinese orchestra, particularly those imbued with values have gone through a variety of arrangements by different composers from different background and with different intentions, coupled with the effects of globalization on music which results in the hybridity of musical styles have made the interpretation process more complex. Other factors which affects the interpretative process such as the technical limitations of the members of the modern Chinese orchestra and the influence of the conductor is also highlighted. As this study is only limited to four schools, future research on other modern Chinese orchestras in secondary schools or schools in other countries could be conducted. This could provide more references, to reveal more insightful information on the performance practice of the modern Chinese orchestra in this country. Research in this area could also contribute to the existing or future modern Chinese orchestra in Malaysia, as the orchestra in schools became a major platform to train musician in Chinese instruments.